Analyses of community stability and inter-specific associations between a plant species with extremely small populations (Hopea hainanensis) and its associated species - Li Zhang; Hai-Li Zhang; Yukai Chen; Mir Muhammad Nizamani; Qin Zhou; Xiting Su (Frontiers in Ecology and Evolution, 2022)
Hopea hainanensis is a large evergreen tree belonging to the family Dipterocarpaceae. It is currently listed as an endangered species on the International Union for Conservation of Nature’s (IUCN) Red List of Threatened Species. It is found primarily on China’s Hainan Island and northern Vietnam. To protect the plant species with extremely small populations Hopea hainanensis and understand its community stability and the inter-specific associations between Hopea hainanensis and other occurring species, we set up 16 quadrats in the areas where wild Hopea hainanensis populations occurred on Hainan Island to investigate the composition of plant species in the quadrats. We used the M. Godron Community stability index to quantify community stability. Based on the two × two contingency tables, the statistic X2, association coefficient (AC), and Pearson correlation coefficient (PCC), percentage co-occurrence (PC), and OI index (OI) analyze the degree of association between Hopea hainanensis and the dominant species in each layer. The results showed that the relationship between Hopea hainanensis and the dominant species in the community was not significant. In addition, there were both positive and negative associations between Hopea hainanensis and other examined six tree species, positive associations with 13 shrub species, positive associations with two herbs, and negative associations with species of 7 species. The connection between Hopea hainanensis and herbs is more complex than that between trees, shrubs, and the dominant species. M. Godron’s stability analysis showed that the community where Hopea hainanensis occurred is relatively unstable (36.84/63.16). The ecology is somewhat fragile, indicating that the community is still at the early or middle stage of competing with other species for resource utilization. The stability of community structure and function is a suitable environment for Hopea hainanensis and finally achieve the purpose of adequate protection, we should choose species with strong positive associations for protecting and recovering Hopea hainanensis.